Fiscal sustainability and policy issues in the Eastern Caribbean Currency Union - Kufa, Phebby (IMF [Washington]US, 2003)
Examines the quantitative and structural guidelines of the ECCB for member countries' fiscal performance, with a view to the convergence needed to support the currency union.